Public private partnerships as an alternative service delivery option : a multiple case study of the healthcare sector - Haarhoff, Kosie Jacobus (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.